UNPLANNED PREGNANCY AND THE IMPACT ON SIBLING HEALTH OUTCOMES. (31st August 2012) - Lordan, Grace; Frijters, Paul
ABSTRACT This work considers whether planning matters with respect to the effect of a new sibling on another siblings' health. Objective health outcomes are observed before and after a new addition to the family. To date, the literature on family size has focused on a quality–quantity trade‐off; the more children in a family, the less resources devoted to each child. We present a theoretical framework which highlights that the quantity–quality trade‐off may only be relevant in the case of an unplanned sibling. We also suggest that a planned sibling may result in health gains for the other children. We use two waves of data for more than 1800 children from Peru from the Young Lives Project to test our hypothesis. The data relate to the children at 1 and 5 years. For health outcomes, height for age and weight for age Z are considered. The results highlight significant negative independent effects on height for age when an unplanned sibling is added to the household. In addition, we find positive sibling effects on height for age when a planned sibling arrives. We find only small planning effects for weight for age. We view our hypothesis as a pathway that can further explain the quantity–quality trade‐off. Copyright © 2012 John Wiley & Sons, Ltd.